Effect of surface preparations on the adhesion and corrosion behaviour of Zn-0.5Al coating on high carbon steel - Chai, Teck Chaw (2014)
The corrosion of steel is one of the primary causes for premature failure. The ideal way to overcome this problem is to provide corrosion protection right at the time of manufacturing by hot-dip galvanizing. Conventionally, pure zinc (Zn) galvanizing provide a poor adhesion coating due to formation of brittle intermetallic of Fe–Zn; whilst single layer Zn–0.5 wt% Al alloy coating has a poor adhesion due to lack of suitable fluxes. This project is aimed to investigate the effects of various surface preparation treatments of high carbon steel plate on the adhesion and corrosion behaviour of Zn-0.5Al coating. Surface preparation prior to coating is thus crucial in order to obtain better coating adhesion and improve corrosion resistance. In this project, sand blasting and sand grinding were conducted together with chemical pretreatment on the steel substrate prior to Zn-0.5Al coating. The sand blasted, sand ground together with chemical pretreated steel samples were coated with Zn-0.5Al coating by dipping process. Adhesion property was examined on the coated samples by using pin on disc test. Electrochemical and salt spray tests were performed on the coated steels following the ASTM standard. Analysis has been carried out on the samples by using standard material characterization techniques namely optical microscopy, scanning electron microscopy and X-ray diffractometer. From this project, it was found that sand blasting followed by chemical pretreatment gave the best coating performance in terms of both adhesion and corrosion protection. This is due to the effect of high surface roughness from sand blasting which led to good mechanical interlocking effect for improved adhesion strength between Zn-0.5Al coating and steel substrate. Subsequently, corrosion protection also improved because Zn-0.5Al alloy coating did not peel off easily during corrosion tests. Sand ground galvanized steel gave the intermediate coating performance and conventional chemical pretreatment galvanized steel had a low coating performance in terms of both adhesion and corrosion protection. It can be concluded that surface roughness has significant effect on the coating adhesion and corrosion protection of galvanized coating.